Phosphatidylinositol(4,5)bisphosphate and Phosphatidylinositol(4)phosphate in Plant Tissues - Irvine, R. F. (1989)
Pea (Pisum sativum) leaf discs or swimming suspensions of Chlamydomonas eugametos were radiolabeled with [(3)H]myo-inositol or [(32)P]Pi and the lipids were extracted, deacylated, and their glycerol moieties removed. The resulting inositol trisphosphate and bisphosphate fractions were examined by periodate degradation, reduction and dephosphorylation, or by incubation with human red cell membranes. Their likely structures were identified as d-myo-inositol(1,4,5)trisphosphate and d-myo-inositol(1,4,)-bisphosphate. It is concluded that plants contain phosphatidylinositol(4)phosphate and phosphatidylinositol(4,5)bisphosphate; no other polyphosphoinositides were detected.